Elementary linear algebra - Anton, Howard (New York : John Wiley & Sons, 2000)
This book is about: Systems of linear equations and matrices; Determinants; Vectors in 2-space and 3-space; Euclidean vector spaces; ...
Keywords: Algebras; Linear of Algebras; Algebra, Linear